A systematic study on microstructure evolution, mechanical stability and the micro-mechanical response of tensile deformed medium manganese steel through interrupted tensile test - Mohapatra S.; Poojari G.; Marandi L.; Das S.; Das K. (My University, 2025)
In the current work, the microstructure evolution, mechanical stability of austenite and the micro-mechanical response of tensile deformed Fe-0.18C-4Al-7Mn (Wt%) steel are investigated. Interrupted tensile tests on the annealed samples (750 °C, 1 h) were performed at a tensile elongation of 5, 10, 20, 30, 40 and 60% to understand the deformation behavior and transformation-induced plasticity (TRIP) effect. Strain-induced martensitic transformation (SIMT) of reverted austenite is explored using X-ray diffraction (XRD), transmission electron microscopy (TEM) and electron backscattered diffraction (EBSD) analysis. The coefficient of mechanical stability of austenite (k-parameter) is quantified through the interrupted tensile tests using XRD analysis. Instrumented nanoindentation test was conducted on individual phases of the interrupted tensile-tested samples to determine their hardness and modulus values. The scanning electron microscopy (SEM) analysis reveals the gradual decrease in width and increase in length of austenite-martensite islands with an increase in the percentage of elongation. Evolution of dislocation lines, dislocation tangles and dislocation accumulations occur at ferrite grain boundaries and martensite lath boundaries during tensile deformation. The volume fraction of austenite decreases, and the transformation of austenite to martensite and dislocation density of austenite increase with the increase in the tensile elongation. Austenite is found to be mechanically more stable at 30% of tensile elongation due to the low austenite transformation ratio. Nanoindentation results show that the hardness increases with an increasing percentage of deformation. Multiple pop-ins are observed in load (P)–indentation depth (h) curves due to dislocation interaction at the interphase boundary. © 2022 Elsevier Inc.